Performance characteristics on patch antenna with sar reduction using artificial magnetic conductor (amc) for wban applications - Omar Mumin, Abdul Rashid (2019)
Great advances have been made in the area of wireless body area networks (WBANs) of improving wireless communication technology since the invention. These advances range in refining, size reduction and shape, gain improvement, more efficiency and combination of the requirements for applications which include health monitoring, military and personal navigation entertainment. Several types of antennas have been developed for WBANs and they have achieved narrow bandwidth, decrease gain, low radiation efficiency, a high specific absorption rate (SAR) value, high front-to-back ratio (FBR) and structural complexity. However, it is necessary to achieve better performance antenna for less impact of frequency detuning, by improving FBR, high radiation efficiency and reduce SAR for WBAN application. Conventional patch antennas are adopted since they can be low weight, low profile and easy to integrate with the device. Having these unique characteristics, patch antenna has shown to have clear advantages for WBAN applications. Since an antenna is placed a close to the human body with its curvatures and complexities, the antenna performance must be taking into account the structural, mismatch, and losses caused by the body, while simultaneously sustaining optimum performance. This work proposes to design, analysis and optimization of low-profile antenna integrated with Artificial Magnetic Conductor (AMC) for WBAN applications. Multilayer model of the adult human body at the frequency band of the proposed antenna is used, which helps to study the effects of the human on the antenna performance. The results showed that the presence of human head affects the antenna performance in terms of radiation pattern, efficiency and S11 and SAR values on the body parts. To further improve the performance of the proposed antenna design, several techniques have been developed in reducing SAR value with low complexity using AMC to realize broadside radiation for on /off body communication. AMC structure and miniaturized reflector reduce the back radiation and the impact of frequency detuning due to high losses of human body and the two proposed techniques are mounted on human head phantom. In addition, AMC improved FBR by 15.3 dB with enhanced of gain 7.61 dBi and radiation efficiency more than 88 %. The AMC have achieved 93.7 % reduction of the initial SAR value while metal reflector achieved a reduction of 77.7 %. Then, the antenna is fabricated and measured to validate the concept. Thus, the proposed antenna with AMC structure was designed and fabricated using two different materials for far-field radiation pattern measurements. The measured and simulated results reveals that proposed antenna with AMC array shows good impedance matching and far-field radiation pattern .Therefore, the proposed antenna is a potential candidate for WBAN.